Strategies for Monitoring Outcomes in HIV-Exposed Uninfected Children in the United Kingdom - Thorne, Claire; Tookey, Pat (Frontiers in Immunology, 2016)
Surveillance of pregnancies in women living with HIV is carried out on a national basis in the United Kingdom (UK) through the National Study of HIV in Pregnancy and Childhood. There are currently around 1100–1200 HIV-exposed uninfected (HEU) infants born every year in the UK, where vertical transmission of HIV now occurs in fewer than 5 in every 1000 pregnancies. By the end of 2014, there was a cumulative total of more than 15,000 HEU children with any combination antiretroviral therapy (cART) exposure and more than 5000 with cART exposure from conception in the UK. HEU infants are increasingly being exposed to newer antiretroviral drugs for which less is known regarding both short- and long-term safety. In this commentary, we describe the approaches that have been taken to explore health outcomes in HEU children born in the UK. This includes the Children exposed to AntiRetroviral Therapy (CHART) Study, which was a consented follow-up study carried out in 2002–2005 of HEU children born in 1996–2004. The CHART Study showed that 4% of HEU children enrolled had a major health or development problem in early childhood; this was within expected UK norms, but the study was limited by small numbers and short-term follow-up. However, the problems with recruitment and retention that were encountered within the CHART Study demonstrated that comprehensive, clinic-based follow-up was not a feasible approach for long-term assessment of HEU children in the UK. We describe an alternative approach developed to monitor some aspects of their long-term health, involving the “flagging” of HEU infants for death and cancer registration with the UK Office for National Statistics. Some of the ethical concerns regarding investigation of long-term outcomes of in utero and perinatal exposure to antiretrovirals, including those relating to consent and confidentiality, are also discussed.